Testing and modelling of the damping effects for fluid-based inerters. (2017) - Liu, Xiaofu; Jiang, Jason Zheng; Titurus, Branislav; Harrison, Andrew J.L.; McBryde, Daniel
Abstract: The inerter is a dynamic physical dual of a capacitor via the force-current analogy, having the property that the force across the terminals is ideally proportional to their relative acceleration. Fluid-based forms of inerter have physical advantages of improved durability, inherent damping and simplicity of design in comparison to mechanical flywheel-based forms. Apart from the inertial effect, linear and nonlinear damping also occur in the helical-tube fluid inerter arrangement. In previous studies, discrepancies between experimental and theoretical results have been found. These are believed to arise from imperfect modelling of damping and pressure losses within the helical tube. To model these effects more accurately, this paper introduces a new experimental set-up. Pressure gauges are used to measure the pressure drop across the helical channel during constant velocity tests. This approach delivers improved agreement between experimental and theoretical results. The sources of minor remaining discrepancies are further analysed. Furthermore, a new fluid-based inerter design is first proposed with different damping characteristics, the theoretical damping comparison is also presented between these two designs.